THE ROLE OF LOCAL COMMUNITY PARTICIPATION IN THE DEVELOPING CULTURAL TOURISM SUSTAINABILITY - Andini Wibowo; Tina Miniawati Barusman; Tri Lestira Putri Warganegara (Program Studi Magister Manajemen, 2023)
This research objective is to determine the forms, degrees, and variables that encourage and impede community participation in the development of sustainable cultural tourism in the city of Bandar Lampung. This type of research uses a qualitative approach, in which the researcher conducts in-depth interviews with informants who are subject matter experts and direct observation. This form of research adopts a descriptive methodology. Tourism development that involves community participation deserves special consideration, particularly in the context of long-term tourism development. The purpose of community engagement in this planning is to transform the community from an object to a subject in a plan to construct tourist attractions in their region. The definition of planning is moving from merely drafting plans to sustainable planning, which includes not only planning before launching an activity but also preparing future stages of development. The researcher can conclude, based on the description and the outcome of the interview, that the community has participated in the planning, management, and usage phases of the development of cultural tourism.